PRODUKSI BIOGAS DARI SUBSTRAT DASAR KOTORAN SAPI, KOTORAN AYAM DAN LIMBAH CAIR TAHU DENGAN INOKULUM RUMEN SAPI - Subhan nuradzan; Umrah; Kasman (Biology Department, Mathematics and natural science, Tadulako University, 2019)
The research of biogas aims to obtain an alternative energy source which might replace fossil energy in the future. It was carried out starting from November 2017 to February 2018 in which was located in Langaleso Village, Dolo Subdistrict, Sigi District and in the Laboratory of Biotechnology, Department of Biology, Faculty of Mathematics and Natural Sciences, Tadulako University. The primary substrates were cow dung, chicken manure and the tofu liquid waste by cow rumen as inoculum. The installation of gas-flowed pipes was conducted by using paralon pipes with size ½ dan ¾ inch with the total lenght 8,40 m. The incubation period of the primary substrates was 30 days where the biogas volume quantification was periodically performed in the day of 10, 20, and 30. The results showed that biogas was formed at the incubation day of 10 which hence increase up to the day of 30. The observed gas volume was 223,568 cm3, 368,950 cm3 dan 458,302 cm3 respectively. The results of flame test representing blue flame indicated that the formed biogas contained the content of methane which higher than 70%. This hence revealed that the installation of biogas reactor with the type of “fixed domed plant” equipped by “watertrap” was able to produce a good quality biogas from the primary substrates were cow dung, chicken manure and the tofu liquid waste by cow rumen as inoculum for the application in the household scale.